2014
DOI: 10.1093/aob/mcu117
|View full text |Cite
|
Sign up to set email alerts
|

Selenium addition alters mercury uptake, bioavailability in the rhizosphere and root anatomy of rice (Oryza sativa)

Abstract: Addition of Se to Hg-contaminated soil can help produce brown rice that is simultaneously enriched in Se and contains less total Hg and MeHg. The lowered accumulation of total Hg and MeHg appears to be the result of reduced bioavailability of Hg and production of MeHg in the rhizosphere, suppression of uptake of Hg into the root cells and an enhancement of the development of apoplastic barriers in the endodermis of the roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 44 publications
5
20
0
Order By: Relevance
“…The presence of chlorosis decreased significantly with increasing Se additions. These results are in line with those for Wang et al (2014), who documented significant increase in brown rice yield after adding 5 mg sodium selenite per kg of Hg-contaminated soil.…”
Section: Do Sodium Selenite Additions Change the Toxicity Of Hg And Asupporting
confidence: 91%
See 2 more Smart Citations
“…The presence of chlorosis decreased significantly with increasing Se additions. These results are in line with those for Wang et al (2014), who documented significant increase in brown rice yield after adding 5 mg sodium selenite per kg of Hg-contaminated soil.…”
Section: Do Sodium Selenite Additions Change the Toxicity Of Hg And Asupporting
confidence: 91%
“…The decreased toxicity of Hg in plants in the presence of Se has been suggested to be due to reduced bioavailability of Hg and consequently reduced production of MeHg in the rhizosphere, suppression of uptake of Hg into the rootcells and an enhancement of the development of apoplastic barriers in the endodermis of the roots (Wang et al 2014). A recent study by Wang et al 2016 confirmed the formation of Hg-Se complexes in soils (detected by TEM-EDX and XANES) and thus reduced microbial MeHg production.…”
Section: Do Sodium Selenite Additions Change the Toxicity Of Hg And Amentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, there is growing evidence that selenium (Se) could efficiently reduce Hg accumulation in rice plants (i.e., Hg-Se antagonism, Zhang et al 2012;Zhao et al 2014;Wang et al 2014a;Li et al 2015). It is proposed that the formation of Hg-Se complexes in soil and/or high molecular weight Hg-Se complexes in rice root could be responsible for the observed Hg-Se antagonism.…”
Section: Introductionmentioning
confidence: 99%
“…The main strategies used by plants to tolerate and minimize detrimental effects of high metal concentrations are to restrict uptake, limit translocation or detoxify through chelation and subcellular compartmentalization to avoid accumulation in the whole plant (Jan and Parray 2016). Root related mechanisms, which may contribute to the Cd reduction uptake, could be an enhanced development of apoplastic barriers in the endodermis of roots and a lower activity of the membrane transporters activity (Wang et al 2014). Moreover, more lignin and thicker cell walls may be formed in cells being exposed to Se (Cui et al 2018) and therefore restrict the translocation of Cd that will be adsorbed.…”
Section: Discussionmentioning
confidence: 99%